2017
DOI: 10.2118/186112-pa
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in Cleanup of Fracturing Fluids Used in Conventional Reservoirs: A Literature Review

Abstract: Summary Fracturing fluids are used for transport and placement of proppants in hydraulic-fracturing operations. In the case of conventional reservoirs, sufficient fluid viscosity is needed to transport proppant. An ideal fracturing fluid should possess enough viscosity to suspend and carry proppant. After the proppant placement, the fluid viscosity should drop to facilitate an efficient and quick fracture cleanup. This ensures adequate fracture conductivity. Most of the fracturing fluids used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Therefore, to reduce the speed of degradation, lower concentrations of these preferred breakers were considered. However, based on related literature and previous experiment judgment, low-concentration cellulase, amylase and pectinase alone cannot completely reduce the viscosity of guar gum polymer [ 1 , 5 , 18 ]. Comprehensive consideration of cost and degradation speed, lower concentrations of mannanase I, mannanase II, and galactosidase breakers were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to reduce the speed of degradation, lower concentrations of these preferred breakers were considered. However, based on related literature and previous experiment judgment, low-concentration cellulase, amylase and pectinase alone cannot completely reduce the viscosity of guar gum polymer [ 1 , 5 , 18 ]. Comprehensive consideration of cost and degradation speed, lower concentrations of mannanase I, mannanase II, and galactosidase breakers were used.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, guar gum is also a relatively low-cost natural material with a high affinity for water [ 4 ]. Guar-based polymers are high-molecular-weight biopolymers, in which the main chain consists of mannose, with galactose as the side chains, such that the ratio of mannose to galactose varies from 1.6:1 to 1.8:1 [ 5 ]. Previous studies have reported that the polymer viscosity, which reflects its stability, exhibits a positive correlation with molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the fracturing fluid rheological properties, its chemical breakage and cleanup characteristics are critical for maintaining a high fracture conductivity. Gel breakers are used to reduce the viscosity of fracturing fluid either by cleaving polymer molecules into smaller fragments or by de-crosslinking the network, which involves removal or rather chelation of the crosslinking molecules [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 So, gel breakers are usually introduced to decompose the fracturing fluid to improve the crude output and environmental benefits during hydraulic fracturing. 5,6 Among them, oxidized breakers like ammonium persulfate (APS) are commonly used for water-based fracturing fluids. [7][8][9] Unfortunately, APS is too reactive, even at moderate temperatures, so adding the APS directly to the fracturing fluids will rapidly reduce the viscosity of the fracturing fluid prematurely and result in sand-out during the well construction process.…”
Section: Introductionmentioning
confidence: 99%